Dampak Perkembangan Teknologi Pertanian Terhadap Perubahan Sosial Masyarakat di Kabupaten Madiun - Putri Maulida; Muryani Muryani; Andhita Risko Faristiana (Pusat Riset dan Inovasi Nasional, 2023)
. This study discusses the impact of the development of agricultural technology for the community which initially traditionally became more modern in Bukur Village, Jiwan District, Madiun Regency, East Java Province. Advances in agricultural technology have brought significant changes to society. The impacts of the changes can change the lifestyle and work of farmers. This study uses a qualitative method where researchers have the aim of analyzing the impact of agricultural technology on social change in society. Social change in society is not a result or product but a process. This process of change is of course the result of an agreement or joint decision taken by an individual or a community group. The decisions taken are of course in accordance with the wishes or expectations of the group so that social change can be realized. However, the application of technology does not always have a positive impact, sometimes there are negative things with several obstacles. Some of the obstacles encountered in the process of community empowerment using technology, one of which is secondary human needs that arise after their primary needs are met.